RELEVANCE OF PROGRAMS FOR ADVANCED TRAINING IN THE FORMATION OF COMPETENCIES OF TEACHER IN KAZAKHSTAN (Scientific journal of the Fergana State University, 2026)
The modern education system, focused on solving the problems of innovative development of the economy, imposes new requirements on the level of professional competence of teachers of educational organizations. Pedagogical education, being the main part of the education system, performs the urgent task of staffing preschool, secondary, additional education, as well as technical and vocational and higher education. The article raises the problem of modernization of pedagogical education, which is determined by the tasks set in state programs, internal laws of development of pedagogical education and prospective needs of development of the individual, society and the state. Specialists trained in the system of pedagogical education are called upon to become bearers of ideas of renewal based on preservation and enhancement of the best traditions of domestic education and world experience. The stated goal of modernization of pedagogical education is the creation of a mechanism for effective and dynamic functioning of pedagogical education in the context of implementation of modernization of Kazakhstan education. According to the authors, the result of modernization of pedagogical education should be an updated system of training, retraining and advanced training of teachers, meeting the requirements of society for teaching staff. Improving the professional level of teachers and forming a teaching staff that meets the demands of society is a necessary condition for modernizing the education system. Education is the most important means and resource for developing a creative personality, capable and ready to live in a multidimensional and rapidly changing society.